Systemic corticosteroids for subcutaneous panniculitis‐like T‐cell lymphoma. (1st October 2014) - Guenova, E.; Schanz, S.; Hoetzenecker, W.; DeSimone, J.A.; Mehra, T.; Voykov, B.; Urosevic‐Maiwald, M.; Berneburg, M.; Dummer, R.; French, L.E.; Kerl, K.; Kamarashev, J.; et al.
Summary: Background: Primary cutaneous γ/δ T‐cell lymphoma (PCGD‐TCL) is aggressive and has a poor prognosis. In contrast, subcutaneous panniculitis‐like T‐cell lymphoma (SPTCL) of the α/β T‐cell receptor phenotype is known to follow an indolent course and have a more favourable prognosis. In the past, PCGD‐TCL and SPTCL were often considered to be a manifestation of the same disease, and aggressive systemic polychemotherapy has commonly been the first‐line therapy for both. Given the understanding that SPTCL is a separate and less aggressive entity, clinical data exclusively evaluating the efficacy of conservative treatment in SPTCL are needed. Objectives: To assess the overall clinical response to systemic corticosteroids in the treatment of SPTCL. Methods: This was a retrospective cross‐sectional study based on a patient data repository from two tertiary care university hospitals in Zürich (Switzerland) and Tübingen (Germany). The repository spanned 13 years. Results: In four of the five patients (80%) with SPTCL, treatment with systemic corticosteroids induced a complete remission. Conclusions: Systemic corticosteroids may be an excellent first‐line single‐agent therapy for SPTCL.